Penggunaan Karbon Aktif dari Tandan Kosong Kelapa Sawit Teraktivasi NaOH pada Penyerapan Ion Pb(II): Utilization of NaOH-Activated Carbon from Oil Palm Empty Fruit Bunches on Pb(II) Ion Absorption - Minda M; Husain Sosidi; Ni Ketut Sumarni; Hardi Ys.; Ruslan; Nov Irmawati Inda; Moh. Mirzan (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2022)
Oil palm empty fruit bunches (OPEFB) are plantation waste that has the potential to be used as activated carbon. The main component of OPEFB is lignocellulosic which can be a source of activated carbon and utilized for Pb2+ ion adsorption. The use of activated carbon activated by NaOH still requires optimization, especially in determining the contact time and optimum adsorption pH. This study aims to determine the effect of pH and contact time on the adsorption of Pb2+ and to determine the efficiency of the adsorbent on the adsorption of Pb2+. In this study, activated carbon from OPEFB was carbonized at 300oC for 1 hour, followed by activation using NaOH 0.5%. The results showed that the use of pH 5 and a contact time of 90 minutes had a relatively higher Pb2+ adsorption than other conditions. However, the use of variations in pH and contact time had no significant effect on the adsorption of Pb2+ ions. Adsorbents with variations in pH 4, 5, 6, 7, and 8 were able to absorb Pb2+ of 99.73%, 99.86%, 99.74%, 99.79%, and 99.80%, respectively. Adsorbents with variations in contact time of 30, 60, 90, 120, and 150 minutes were able to absorb Pb2+ of 99.28%, 99.40%, 99.48%, 99.44%, and 99.48%, respectively.